The role of CBT in enhancing health outcomes in coronary artery bypass graft patients: a systematic review - Danya Ibrahim; Ibrahim H. Elkhidir; Zainab Mohammed; Da’ad Abdalla; Omer A. Mohammed; Lina Hemmeda; Salma Alrawa; Mohamed Ahmed; Rahma Abdalla; Abrar Batran; Zaynab Abdalla; Nida Bakri Elhaj; et al. (BMC Psychiatry)
Abstract Background Coronary artery bypass graft (CABG) is a common intervention for managing coronary artery disease, which is often accompanied by postoperative psychological challenges such as anxiety and depression. This systematic review aims to evaluate the benefits of cognitive behavioral therapy (CBT) in reducing anxiety and depression symptoms and improving overall health outcomes in patients’ post-coronary artery bypass graft (CABG) surgery. Methods A search of Science Direct, PsycINFO, PubMed, Google Scholar, VHL, Cochrane, and Scopus databases was conducted until October 2023. Inclusion criteria encompassed randomized controlled trials reporting on CBT or CBT-based interventions tailored for CABG patients, with anxiety and depression symptoms, as well as quality of life, as primary outcomes. Hospital stay and satisfaction with therapy were considered secondary outcomes. Results The findings highlighted that CBT led to improvements in anxiety and depression symptoms, as well as reduced hospital stays, lowered hopelessness levels, and increased satisfaction with therapy. The long-term effects of CBT on CABG patients need to be studied, focusing on larger samples and patient compliance. Furthermore, assessment of CBT implementation in real-world clinical settings is important for feasibility, acceptability, and effectiveness across different regions. Conclusion This review underscores the positive impact of CBT on mitigating depression and anxiety symptoms and boosting the quality of life of individuals post-CABG surgery.